Towards an Ontological-based CIM Modeling Framework for IoT Applications - Bettaz, Mohamed; Maouche, Mourad (Informatica, 2025)
Few works addressed contributions of ontologies to Computation Independent Modeling (CIM) of Internet of Things’ (IoT) applications. This work targets CIM artefacts developed using a combination of a goal-oriented requirements (KAOS) and a service-oriented (SoAML) modeling frameworks. This paper proposes an ontological-based framework intended to help CIM modelers in their preliminary analysis of IoT applications. We adopt the ontology reuse approach, an approach often used by the ontology engineering community, where specific ontology fragments are selected, adapted and/or refined, and merged. We use OntoUML to describe our fragments. The OpenPonk tool is used to edit and verify the syntax and the semantics of these fragments’ models. The results of our contribution are summarized as follows. Improving the semantics carried by the metamodels of KAOS and SoaML modeling languages, through our proposed conceptualization grounded by the Unified Foundational Ontology (UFO), a sound ontological framework; setting a link between our proposed KAOS and SoaML ontology fragments; designing a (partial) IoT domain ontology to be integrated into our proposed CIM. An illustrative example, showing how to instantiate selected ontology fragments, demonstrates the applicability of our results to IoT applications.